KAJIAN KRITIS TERHADAP TEORI SUMBER-SUMBER: TINJAUAN JULIUS WELHAUSEN (DOCUMENTARY HYPOTHESIS) - Christon Nababan; Wilda Prianty Simanjuntak (Moriah Theological Seminary, 2026)
The Pentateuch contains the first five books in the Old Testament, namely Genesis, Exodus, Leviticus, Numbers and Deuteronomy. These five books, according to the view of the layman, especially by the Batak, are written by Moses because indirectly the Bible (the Bible in Batak) writes the name of this book with 1 Moses to 5 Moses. The research method is carried out through the descriptive qualitative method, namely with literature, both through journals and even books written by Julius Wellhausen himself and not forgetting the books of other theologians. These five books were not only written by Moses but according to Julius Wellhausen there are five groups in the writing of this book, namely Yahwis (Y), Elohis (E), Deuteronomists (D), and Priests (P) where this plays a role in the process of canonization of these five books which lasts even centuries until the Pentateuch itself is formed.